RESEARCH ON ELASTIC MESHING EFFECT OF RV DRIVE WITH BEVELOID GEAR - DENG ShiWei; DU XueSong; ZHU CaiChao; YU ZiQiang; HUANG YuCheng (Jixie qiangdu)
Finite element contact analysis of a planetary drive with small teeth difference in a beveloid gear RV drive was carried out. The results show that the meshing performance differs from that of the traditional gear design theory result. The effect of elastic meshing under different loads on the axial force,contact force,number of actual contact teeth,load distribution among the teeth,contact stress of the tooth surface and tooth root stress. The results of the analysis provide the basis for improving the bearing capacity,gear parameter optimization,tooth profile modification and the strength calculation of parts with small teeth difference.